Computational studies on design optimization for Saccardo nozzle in tunnel ventilation. (December 2021) - Hang, Joo Guan; An, Hui; Wang, Peng Cheng; Yu, Simon Ching Man; Chan, Samuel; Thong, Melvyn; Lim, Lean Wan; Cheong, Mun Kit; Louis, Gerald
Highlights: CFD simulation was carried out to study the Saccardo nozzle design in road tunnels. A tunnel temperature prediction model was developed to study the carry-over effect. Various nozzle designs were evaluated in terms of nozzle efficiency and power. Air bleed design showed reduced tunnel temperature and improved nozzle efficiency. The nozzle efficiency was shown to be highly correlated to the power consumption. Abstract: Longitudinal ventilation system with Saccardo nozzles has been widely used to ventilate long road tunnels to maintain acceptable air quality and thermal comfort. The design of Saccardo nozzle impacts the ventilation power consumption, nozzle efficiency and momentum exchange in the tunnel, which inherently affects the tunnel air temperature. This paper presents a detailed study of the performance of an optimised Saccardo Nozzle design using Computational Fluid Dynamics (CFD) simulation. The CFD model was combined with a mono-dimensional temperature prediction model to evaluate the carry-over effects in the tunnel. The impact of various tunnel design parameters was parametrically evaluated to identify the key important geometric parameters that affect the Saccardo nozzle performance. The design of the nozzle was finally optimized under constant power consumption conditions and compared against that in an existing baseline road tunnel. The optimized nozzle design shows a significant reduction in the overall maximum tunnel air temperature. The nozzle efficiency shows a 9% improvement. In addition, an alternative nozzle design was also proposed by introducing air bleeds underneath the Saccardo nozzle. The air bleeds design could further reduce the tunnel air temperature by 6% with a 5% improvement in the nozzle efficiency. The air bleeds design is considered to be a feasible solution to be adopted into the existing tunnel with minimal modification work required.